MEMORY FORENSIC DEVELOPMENT AND CHALLENGES IN IDENTIFYING DIGITAL CRIME : A REVIEW - Azzery, Yasep; Dwi Mulyanto, Nur; Hidayat, Taufik (TEKNOKOM, 2022)
Digital forensic technology is currently advancing along with the demands to uncover various crimes using technology. Memory Forensic is one of the investigative fields in digital forensics. We use the Systematic Literature Review method to identify the developments and challenges of Forensic Memory in identifying digital crimes, analyzed from various reference papers according to the Include and Exclude Criteria and based on the specified Research Question. Authors chose from 30 reference journals from 3 online journal databases namely IEEE Explore, Sciencedirect, and Springer with themes related to forensic memory based on certain criteria for further review to determine the development of digital crime. The results of the SLR that we convey are the result of a study related to the use of Memory Forensic in identifying various digital attacks and challenges faced in the future.